Knee pain in children as a symptom of hip disease: a case study - Katarzyna Toś; Aleksandra Winiarz; Paula Szlendak; Wojciech Wokurka; Michał Turek; Kacper Wojtala; Sylwia Grosman; Agata Węgrzyniak; Dominik Drobek; Katarzyna Wąsala (Kazimierz Wielki University, 2023)
Introduction  Knee pain in the pediatric population is a very common health issue in family doctor practice and its cause is not always obvious and easy to determine. It is important to remember that knee pain can also occur as a projection of the obturator nerve conducting signals from the hip joint. During physical examination the hip joint should be also carefully examined. Diagnostic imaging such as radiographs are helpful in evaluating bone parts, whereas ultrasonography and MRI can reveal pathology in periarticular soft tissue. Laboratory tests can help to rule out a septic process and reveal other associated conditions.  The aim  The aim of this work was to analyze the patient's case of transient synovitis of the hip manifested by knee pain and discuss other hip joint causes of knee pain in the pediatric population. Case report An individual case report of the five-year-old male patient suffered from non-traumatic knee pain and inability to walk with analysis of undertaken diagnostic and treatment management. Results The patient was correctly diagnosed with transient synovitis of the hip joint and successfully treated due to a thorough physical examination and right diagnostic tests carried out by the emergency physician. Conclusions In every case of non-traumatic knee pain, hip pathology should be always ruled out. Carefully performed physical examination, basic laboratory tests and imagining allow practitioners to make the right diagnosis.